Digitalization of Management Information Systems at Intuition Bookstore Makassar City - Asriyani Ismail (Asian Journal of Applied Business and Management, 2023)
Along with the development of the business world, computers have an important role in facilitating the completion of a job and helping to develop a maximum service system to support company performance, one of which is by building an information system. The process of managing book data can run smoothly and produce precise and accurate information, a digitization system is needed that can process the book management system as a whole in order to minimize errors that often arise. The purpose of this research is to design a desktop-based INTUISI bookstore management information system. The design method uses the UML method with the data analysis process using the PIECES method. The result is that the management digitization process at the INTUISI bookstore becomes easier and more efficient in reporting the management that occurs, this can be seen from the results of the User Acceptance Test (UAT).